Pilgrimage and the Jews - Gitlitz, David M. (Praeger, 2006)
1. Jewish pilgrims? -- 2. Beginnings : converging on Jerusalem -- 3. Jerusalem, the state cult, and the three harvest pilgrimages -- 4. Pilgrimage in the early diasporas -- 5. Life on the pilgrimage road -- 6. Oh, Zion : Jerusalem in the center -- 7. Jewish saints be praised! -- 8. The cult of the Rebbe : Hasidic pilgrimage -- 9. Praying at the tzadiq's tomb : Sephardic pilgrimage -- 10. The shrines of the Holocaust -- 11. The shrines of nationhood -- 12. Israel as a shrine for the diaspora -- 13. Roots pilgrimage -- 14. Shrine wars.